2022
DOI: 10.1021/acsami.2c16766
|View full text |Cite
|
Sign up to set email alerts
|

Candied Haws-Like Fe–N–C Catalysts with Broadened Carbon Interlayer Spacing for Efficient Zinc–Air Battery

Abstract: As efficient nonprecious metal catalysts for oxygen reduction reaction (ORR), Fe−N−C materials are one of the most promising alternatives to Pt-based catalysts for fuel cells and metal−air batteries. However, the intrinsically low density of key active sites like FeN 4 moieties hampers their commercial applications. Herein, we provide a smart strategy to construct a candied haws-like Fe−N−C catalyst (CH-FeNC) with broadened carbon interplanar spacing (>4 Å), starting with trehalose as a structure-built brick c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Rechargeable zinc-air batteries (ZABs) are highly preferred for their high specific energy density, security, and low contamination. However, their commercial application is constrained by the inefficiency of oxygen conversion processes at the air electrode. Currently, Pt-based catalysts are widely applied to oxygen reduction reaction (ORR). The atomic layer deposition (ALD) method was used to put the Pt nanoparticle load on CNTs by Gan et al, which obtained a Pt/CNT catalyst with excellent ORR catalytic activity. Meanwhile, Ru or Ir-based catalysts are applied to oxygen evolution reaction (OER). , A highly universal wet-chemical approach was used to prepare RuO 2 nanowires (NWs) by Yang et al, which showed a lower OER overpotential under acidic and alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Rechargeable zinc-air batteries (ZABs) are highly preferred for their high specific energy density, security, and low contamination. However, their commercial application is constrained by the inefficiency of oxygen conversion processes at the air electrode. Currently, Pt-based catalysts are widely applied to oxygen reduction reaction (ORR). The atomic layer deposition (ALD) method was used to put the Pt nanoparticle load on CNTs by Gan et al, which obtained a Pt/CNT catalyst with excellent ORR catalytic activity. Meanwhile, Ru or Ir-based catalysts are applied to oxygen evolution reaction (OER). , A highly universal wet-chemical approach was used to prepare RuO 2 nanowires (NWs) by Yang et al, which showed a lower OER overpotential under acidic and alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%